Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Nilai Perusahaan pada Industri Food and Beverage - Olivia Oktaviani; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of profitability on firm value, liquidity on firm value, and leverage on firm value in the food and beverage industry listed on the Indonesia Stock Exchange for the period 2014-2018. The data used in this study are secondary data obtained from the Indonesia Stock Exchange website. The number of samples used were 17 banking companies that were selected through purposive sampling. The data analysis method used is multiple regression. The classic assumption test used in this study was heterocedasticity test and multicollinearity test. The results of this study are 1) profitability measured using Return on Asset has an effect on company value measured using Price to Book Value, 2) liquidity measured using Quick Ratio has an effect on company value measured using Price to Book Value, and 3) Leverage measured using the Debt to Equity Ratio affect the firm value measured using Price to Book Value.